Ver Schulz: metamorfoses de um projeto artístico - Dantas, Élida Mara Alves (2014)
This study configures as a dip in the universe of the multifaceted Polish artist Bruno Schulz (1892-1942), graphic designer, painter, illustrator, poet, literary critic and writer of the interwar period, born in the town of Drohobycz and killed in one of its streets during World War II. Recognized in the whole world, though little known in Brazil, Schulz stands out by his versatility, the peculiarities of his biography, and especially by his short but significant literary production, took by many as a \"fantastic saga\". Examining deeply his fictional works and making use of his critical essays, this study affirms his philosophical postulate about the principles that guide questions such as the relationship between representation and reality as an audacious Artistic Project and his fictional production as his Literary Project, a deployment of his philosophy in his work with the literature. Articulating such projects and using the theme of metamorphosis as a reading operator, with the help of some of his successors - writers, filmmakers and a graphic artist who, on their way, and the way of specificity of art that is represented by them, these artists have adapted works from the Polish writer - this dissertation investigates how, in Bruno Schulz hands, art becomes a powerful way of mystification of reality.